Psychological Well-being of Islamic Boarding School (Pesantren) Students: The Role of Family Functioning and Self-Compassion in Reducing Loneliness - Intan Islamia; Nadia Nur Fadhilah; Abdul Malik Ghozali; Andry Rahman Arif (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Changes in the living environment and parental separation can trigger various emotional problems in students, including loneliness. This study quantitatively assessed the connection of family functioning, self-compassion, and loneliness to students’ perceptions of family and self among 76 students. Data was collected using psychological scales of loneliness (15 items, α=0.856), family functioning (28 items, α=0.855), and self-compassion (16 items, α=0.796). SPSS 24.0 for Windows was utilized for multiple regression analyses to explore relationships among the variables. Multiple regression analyses revealed significant negative associations between family functioning (β=−0.37,p<0.01), self-compassion (β=−0.521,p<0.01), and loneliness. Family functioning and self-compassion together accounted for 47.1% of the variance in loneliness (R2=0.471). This ascertained the need for proper and family-oriented self-compassion, particularly regarding alleviating loneliness for students who have been distanced from their families. This highlighted the need to employ comprehensive techniques and approaches to enhance the emotional support provided by families and various stakeholders to students. Keywords: psychological well-being, family functioning, self-compassion, loneliness, boarding school